Khirbat Faris : rural settlement, continuity and change in southern Jordan : the Nabatean to modern periods (1st century BC - 20th century AD). - McQuitty, Alison, (Archaeopress Archaeology, 2020)
This volume is the first of three which chart the temporal and spatial occupational fluctuations at the site of Khirbat Faris in Southern Jordan and the stories of the communities that lived there. The excavation report follows the site and its environs throughout their many phases of use and occupation, from the 13th century BC to the present day.